Metallic Biosorption Using Yeasts in Continuous Systems - Karla Miriam Hernández Mata; Onofre Monge Amaya; María Teresa Certucha Barragán; Francisco Javier Almendariz Tapia; Evelia Acedo Félix (International Journal of Photoenergy)
Mining effluents were found to be the main source of pollution by heavy metals of the surface water in the San Pedro River in Sonora, Mexico. The overall objective of this study was to determine the biosorption of Zn, Cu, Mn, and Fe with yeasts isolated from San Pedro River in a continuous system. The tests conducted in two reactors packed with zeolite connected in series. The first reactor was inoculated mixing two yeasts species, and the effluent of the first reactor was fed to second reactor. Subsequently, the first reactor was fed with contaminated water of San Pedro River and effluent from this was the second reactor influent. After 40 days of the experiment a reduction of 81.5% zinc, 76.5% copper, manganese 95.5%, and 99.8% of iron was obtained. These results show that the selected yeasts are capable of biosorbing zinc, copper, manganese, and iron under these conditions.